2010
DOI: 10.1111/j.1537-2995.2010.02830.x
|View full text |Cite
|
Sign up to set email alerts
|

Weak D and DEL alleles detected by routine SNaPshot genotyping: identification of four novel RHD alleles

Abstract: The SNaPshot assay described herein is a helpful supplementary tool for resolving doubtful RhD serology. By allowing accurate identification of weak D and DEL alleles this assay should allow better management of the donors and the patients genotyped weak D Types 1, 2, 3, and 4.1 who can receive D+ blood units.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 40 publications
(57 reference statements)
1
38
1
1
Order By: Relevance
“…The C‐terminal cytoplasmic domain of RhD has been experimentally demonstrated to interact with Domain 2 of ankyrin‐R 16 , and multiple amino acid substitutions (including P411 that would be removed by the large deletion) introduced into the C‐terminal cytoplasmic domain of RhD by directed mutagenesis have been reported to be associated with a reduced expression of the RhD antigen in model systems 17 . In addition, one RHD missense mutation, F410V, which would also be removed by the deletion, was reported to be associated with a weak D phenotype 18,19 . Thus, the replacement of eight amino acids by another four ones in the extreme C‐terminal end of RhD (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The C‐terminal cytoplasmic domain of RhD has been experimentally demonstrated to interact with Domain 2 of ankyrin‐R 16 , and multiple amino acid substitutions (including P411 that would be removed by the large deletion) introduced into the C‐terminal cytoplasmic domain of RhD by directed mutagenesis have been reported to be associated with a reduced expression of the RhD antigen in model systems 17 . In addition, one RHD missense mutation, F410V, which would also be removed by the deletion, was reported to be associated with a weak D phenotype 18,19 . Thus, the replacement of eight amino acids by another four ones in the extreme C‐terminal end of RhD (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…An up‐to‐date review of the literature and the RhesusBase was performed . On the basis of their position relative to the constitutive SSs, 15 variations of the RHD gene, including eight exonic (i.e., first, antepenultimate and penultimate position of exons) and seven intronic variants were selected for functional analysis (Table ).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, we did not find any variants in the entire coding sequences, the exon‐intron boundaries, and the proximal 5′‐UTR and 3′‐UTR of the RHD gene in 6.3% (n = 51) of the 806 samples analyzed. (A recent study reported that in three of 23 samples in which a SNaPshot assay failed to detect mutations, no nucleotide changes in the full coding sequence of the RHD gene were found by sequencing 8 …”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…Two particular concerns, namely, 1) that red blood cells (RBCs) of these phenotypes may cause anti‐D immunization when transfused to D– recipients 3‐7 and 2) that serologic determination of these phenotypes are often not clear cut, make genetic analysis of the RHD gene highly desirable. To date, more than 100 weak and partial D alleles have been registered in the Rhesus Site, with new ones being steadily reported 8,9 . Here, we report 17 novel RHD alleles resulting from a systematic variant screening in a large cohort of subjects with doubtful D phenotypes.…”
mentioning
confidence: 91%